ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI TERAPI RELAKSASI OTOT PROGRESIF PADA DEWASA HIPERTENSI YANG MENGALAMI KECEMASAN DI RT 02 RW 13 KELURAHAN RAGAJAYA, KECAMATAN BOJONGGEDE, BOGOR - Ariyana Pramitha Haryani, (2022)
Anxiety disorders in Indonesia are included in mental and emotional disorders, there were 6.1% anxiety levels in 2013 and 9.8% in 2018, an increase of 3.7% over the last 5 years. Chronic diseases such as hypertension can cause physical, psychological, social problems, mental health problems that are often associated with anxiety in the community are high blood pressure. Progressive Muscle Relaxation. The purpose of this study was to determine whether the intervention of innovative progressive muscle relaxation therapy had an effect on overcoming anxiety in adult patients with hypertension at Rt 02 Rw 13, Ragajaya Village, Bojonggede District, Bogor. After 2 sessions of progressive muscle relaxation therapy, the patient was asked to fill out the current anxiety questionnaire again. The difference in changes in the questionnaire scores in the two patients was due to psychosocial factors, namely perceptions of perceived anxiety.